FULMİNAN KARACİĞER YETERSİZLİĞİ: ETYOLOJİK, KLİNİK VE PROGNOSTİK ÖZELLİKLERİ - ÖZDEMİR, Sebati; Akın, Perihan (Cerrahpaşa Medical Journal, 2014)
Background.- Fulminant hepatic failure is a clinical syndrome with high mortality, characterized by the rapid onset of severe hepatocellular dysfunction, often accompanied by hepatic encephalopathy, in the absence of preexisting liver disease. Although many reasons may cause fulminant hepatic failure, the most common causes of the syndrome are hepatitis viruses, toxin and drugs. The mortality of fulminant hepatic failure is still high despite improvements in the medical emergency care and liver transplantation. This article examines the etiological, clinical and prognostic features of the syndrome as well as its complications.